Union of Foot/Ankle Arthrodesis: A Registry Study of Low-Intensity Pulsed Ultrasound (LIPUS) - Neil J. White; Johnny T. Lau MD, MSc; Kevin Ong; Steven M. Kurtz; Sheldon S. Lin MD (Foot & Ankle Orthopaedics, 2020)
Category: Ankle; Hindfoot; Midfoot/Forefoot; Trauma. Introduction/Purpose: To aid in healing and avoid costly revision surgery, bone grafts, growth factors, and bone stimulation devices are used as adjuncts to foot/ankle arthrodesis. This study evaluated the union rates of LIPUS as an adjunct to foot/ankle arthrodesis and the corresponding factors associated with improved healing. Methods: Foot/ankle arthrodesis patients were identified retrospectively from a prospective post-market arthrodesis/fracture registry for EXOGEN (Bioventus LLC, Durham, NC). Inclusion criteria were males or non-pregnant females 18 years of age or older at time of enrollment, known date of fracture, known start and end dates of LIPUS treatment, and known treatment success outcome. Treatment success was defined by both clinical (solid and pain-free on manual stress) and radiological (at least 3 of 4 cortices bridged on x-rays) criteria. Association between union rates and surgical treatments, comorbidities, and medications was tested with Chi-square tests. Results: A total of 235 primary and 16 revision foot/ankle arthrodesis patients used EXOGEN. 41.4% used EXOGEN within 90 days of the fracture/arthrodesis. Overall union rate was 86.9% (primary: 86.4%; revision: 93.8%). Having the comorbidity of diabetes, obesity, or current smoker was not associated with a higher non-union rate (p=0.779). Other comorbidities were also not associated with increased non-union rates (e.g., Charcot disease p=0.614, NSAID p=0.862, steroids p=0.647). EXOGEN use within 90 days of the fracture/procedure date was associated with improved union rates for the overall (p=0.004, odds ratio (OR) 3.7 (95% CI: 1.5-9.3)) and primary (p=0.007, OR 3.4 (95% CI: 1.3-8.6)) groups. For the overall group, union rates were 94.2% (EXOGEN use <=90 days post-fracture/procedure), 80.6% (91 to 365 days), and 84.6% (>365 days). Conclusion: Union rates for foot/ankle arthrodesis with adjunctive LIPUS were comparable to other therapies with and without other adjuncts (Table 1). Known risk factors for non-union, such as smoking and Charcot disease, were not found to be associated with healing for the LIPUS patients. This suggests the possibility that LIPUS was able to mitigate potential patient risk factors and may offer a low risk post-operative adjunct in difficult healing scenarios.